Monitoring the performance of state structure plan in delivering output using dynamic model - Abdullah, Muhammad Faris; Abdullah, Alias; Zahari, Rustam Khairi; Jaafar, Samsuddin (Malaysian Institute of Planners, 2016)
Plan outputs are the material objects that are tangible and provided as a result of the implementation of a development plan. They often act as precursor to achieving plan outcomes. Therefore, it is important to monitor the performance of plan in delivering its outputs so that the prospect of achieving its outcomes remains high. However, present state structure plan monitoring programmes focus mostly on monitoring land use change and not plan output delivery. The absence of output monitoring reduces the usefulness of the programmes and contributes to under-provision of outputs, especially public facilities and open spaces. This study proposes that state structure plan monitoring programmes must include mechanism to monitor the performance of the plan in delivering plan outputs. To this end, a dynamic model for monitoring performance of state structure plan in delivering open spaces was developed using STELLA software and applied on the Selangor State Structure Plan. The model simulation showed that the Selangor State Structure Plan has performed poorly in delivering the open spaces where their provision has not conform to the plan’s targets. The model simulations also show that this nonconformances will remain by the end of the plan’s planning period.